Increasing Nila Crispy Production Capacity in Bobosan Village, West Purwokerto District, Banyumas Regency - Sutarmin; Siti Badiatul Umroh; Eri Nanda Dewi Purwanti; Kharisma Nurmeilinda (Universitas Muhammadiyah Purwokerto, 2024)
The existence of an upstream fisheries industry in the form of fish farming, the downstream industry in the form of fish processing has enormous potential to be developed. One of the objectives of fish processing is to provide added value to fishery products and as a solution if there is overproduction of fishery products. One of the Crispy Tilapia producers in Bobosan Village that continues to actively process processed fish products is SARMILA SMEs. As time goes by, market demand is getting higher and these SMEs are increasingly overwhelmed because their products are in great demand by the community. In addition to productivity problems, there are weaknesses in business management aspects, especially supply chain management and raw material inventory. The approach offered to overcome these problems was to provide business management training, supply chain management training, and procurement and training on the use of efficient and technologically appropriate production process equipment, such as high-pressure cookers, spinners, and large-capacity pans. With this method, there was an increase in production capacity to 40% or equivalent to 24.5 kg of products or 30.8 kg of raw materials each week from the previous capacity of 17.5 kg of products or 22 kg of raw materials per week.